Assessment of knowledge of and attitudes towards evidence-based clinical practice among nurses - Gotlib, Joanna; Belowska, Jarosława; Żmuda-Trzebiatowska, Halina; Kot-Doniec, Barbara; Panczyk, Mariusz; Zarzeka, Aleksander (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Modern nursing practice providing the most efficient care and patient safety should be based on evidence. Aim. To analyse the level of knowledge and attitudes towards Evidence-Based Nursing Practice (EBNP). Material and methods. 548 nurses (74% of women) taking a state examination organised in summer semester 2014. Return rate: 37%. Mean age: 42 years (min. 35, max. 56, SD = 8.455). 31% — Master’s degree. 22% — secondary education, 17% — a Bachelor’s degree. The length of service: 16.9 years (min. 10, max. 37, SD = 4.979). 51% worked in the public sector, 56% — under an employment contract. 30% worked in a department of general hospital, 16% — in a teaching hospital. Senior nurses: 22%. A voluntary survey. An anonymous standardised questionnaire: „Evidence-Based Practice Profile Questionnaire” (Australia). Cronbach’s alpha coefficient. Descriptive statistics. Results. Cronbach’s alpha coefficient: 0.905. 42% were familiar with the meaning of the EBP and 34% found EBP to be a modern way of practising the profession. 36% were going to use scientific literature to update knowledge, 41% said that scientific reports are useful in professional activity, and 33% said that EBP improves the quality of their professional practice. 39% reported that EBP requirements may have limited use in everyday practice. Conclusions. A questionnaire was an efficient method for measuring the level of knowledge of and attitudes towards EBNP. The attitudes towards EBNP were positive, even though the knowledge required supplementation. Difficulties in using EBNP in clinical practice are objective and require changes to the system of nursing care.  Nursing Topics 2015; 23 (2): 177–182